In Vitro Biological Activity and In Vivo Human Study of Porcine-Placenta-Extract-Loaded Nanovesicle Formulations for Skin and Hair Rejuvenation - Kritsanaporn Tansathien; Tanasait Ngawhirunpat; Worranan Rangsimawong; Prasopchai Patrojanasophon; Praneet Opanasopit; Nopparat Nuntharatanapong (MDPI AG, 2022)
Porcine placenta extract (PPE) contains many water-soluble macromolecular compounds, such as proteins and growth factors, which have limited transportation through the skin. This study aimed to assess the effect of porcine-placenta-extract (PPE)-loaded nano-transdermal systems for skin repair and hair growth promotion. The potentials of the nanoformulation for cytotoxicity, cell proliferation, intracellular reactive oxygen species (ROS) reduction, lipoxygenase inhibition, intracellular inflammatory cytokine reduction, and cell aggregation were evaluated. PPE-entrapped niosome nanovesicles were produced by thin-film hydration and probe-sonication methods, followed by incorporation in a skin serum formulation. The physicochemical properties of the formulation were examined, and the efficacy of the serum formulation was elucidated in humans. The results showed that PPE had no toxicity and was able to induce cell growth and cell aggregation. In addition, PPE significantly decreased intracellular ROS, inhibited lipoxygenase activity, and reduced the production of intracellular tumor necrosis factor-α. In the in vivo human study, the PPE nanovesicles-loaded serum could improve skin properties by increasing skin hydration. Moreover, it was capable of promoting hair growth by increasing hair elongation and melanin index after application for one month. Consequently, the PPE nanovesicles-loaded serum was effective for skin anti-aging and hair rejuvenation.